PERBEDAAN ADVERSITY QUOTIENT PADA MAHASISWA YANG MENGIKUTI OBJECTIVE STRUCTURED CLINICAL SKILLS EXAMINATION (OSCE) BERDASARKAN MOTIVASI BERPRESTASI - , KHALIA FEBRIYANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Objective Structured Clinical skills Examination (OSCE) is the most effective method to evaluate clinical skills assesment on giving safety nursing practice in objective and structured assesment. The research about has been developed pointing to student perception towards OSCE. OSCE makes the student level of stress become higher. And this is another challange for students. Therefore, student need skills which can support OSCE success in term of adversityquotient and achievement motivation, this is required abilities on the self of students to support of success in OSCE. Objective: The purpose of this study was to determine difference of adversity quotient in students who participate on Objective Structured Clinical Skills Examination (OSCE) based on achievement motivation. Methode: Cross-sectional study conducted in 186 students year 2010-2012 was taken through proportional stratified random sampling technique at Nopember-December 2013. Achievement motivation was assessed using Achievement Motivation Scale modification and whereas Adversity Quotient was using Adversity Response Profile. Results: The result of two way ANOVA showed there was difference significant (p<0.05) on the student AQ level year 2010-2012 which has been following OSCE based on achievement motivation with p=0.039 and there was significant association between AQ and achievement motivation p=0.005 (p<0.05). Majority of students had high level AQ in the OSCE (70,4%). Level of achievement motivation of the students mostly (67.7%) belonged to high. Conclusion: There was significant difference of adversity quotient in students who participate on Objective Structured Clinical Skills Examination (OSCE) based on achievement motivation.